Justicia alterna desde un escenario judicial - Negron Martinez, Mildred E.; Velez Fernandes, Lilyana; Gatell Gonzalez, Manuel; Romero Velilla, Ana Elena (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The main objective of this brief report was to share our experience, which started 19 years ago, with the creation, establishment and development of two programs. In the first one, mediation is used as the intervention method for a diversity of conflicts. The main purpose of the second one is developing the public policy of the Judicial Branch pertaining to the use of mediation, arbitration and early neutral evaluation as alternative dispute resolution methods to the adjudication process that is typical of our court system. Both programs respond to a non-adversarial paradigm which is contrary to the adversarial paradigm that contextualizes supports the judicial setting that houses both programs. One of the outstanding outcomes of our experience has been the successful integration of these programs that, in spite of stemming from opposite paradigms, share a common goal: to serve as a forum for the conflict resolution.